The protective effect of p-coumaric acid on toluene-induced hepatotoxicity, nephrotoxicity and neurotoxicity in rats - Fatma Sahindokuyucu-Kocasarı; Selinay Basak Erdemli-Kose; Zeki Erol; Simge Garlı (Revista Colombiana de Ciencia Animal Recia, 2021)
Objective. The aim of this study was to determine the protective effect of p-coumaric acid (p-CA) against toluene-induced hepatotoxicity, nephrotoxicity and neurotoxicity in rats. Materials and methods. A total of 32 Sprague-Dawley male rats, 8 in each group, were used. 4 groups were formed as control, toluene, p-CA and toluene+p-CA. Animals in the control group, toluene group and p-CA group were given 0.9% NaCl, 0.9 mg/kg b.w toluene and 100 mg/kg b.w p-CA orally for 21 days, respectively. The animals in toluene+p-CA group were received p-CA for 3 days and from day 4, toluene and p-CA were applied together daily until day 25. On the 25th day, the study was terminated, blood and tissue samples were collected. Aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatinine levels in serum, glutathione peroxidase (GSH-Px) activity and malondialdehyde (MDA) and glutathione (GSH) levels in the tissue samples were determined. Results. In this study, it was determined that there were significant increases in ALT and AST activities, and creatinine levels in toluene-induced group compared to control group. Moreover, there was a decrease in the GSH-Px activities and GSH levels, and an increase in the MDA levels compared to the control group. However, in the toluene+p-CA group, significant decreases in aminotransferases activities, creatinine and MDA levels, and significant increases in GSH-Px activities and GSH levels were determined compared to the toluene group. Conclusions. It has been determined that p-CA has a protective effect against toluene-induced hepatotoxicity, nephrotoxicity and neurotoxicity.